GENITAL TRACT MALIGNANCIES IN POSTMENOPAUSAL WOMEN - Khursheed, Farkhunda; Jatoi, Nasreen; Das, Chandra Madhu (Journal of Ayub Medical College Abbottabad, 2010)
Background: The most common malignancy in women is breast carcinoma. The next common cancer is genital tract malignancies which constitute 14% of cancers in women. Objective of this study was to determine the type and frequency of genital tract malignancy in postmenopausal women and to find the age distribution of genital tract malignancies. Methods: This descriptive cross sectional study was conducted in Department of Obstetrics ad Gynaecology Unit-II at Liaquat University of Medical and Health Sciences, Jamshoro. All postmenopausal women, admitted in the unit due to various pathologies (abdominal masses, bleeding P/V etc.) from January 2005 to December 2007 were included in the study. Clinical evaluation and investigations were done on all patients. Those women who had benign diseases were excluded from the study. Malignancy was confirmed from histopathology report of biopsy specimen. These women were divided into 3 age groups: group I <60 years, group II 60 to 70 years and group III >70 years. Results: Out of 265 postmenopausal women admitted in ward during the study period, malignancy was confirmed in 68 cases (25.66%). The type of malignancy was cervical carcinoma (41, 60.28%), ovarian carcinoma (11, 16.17%), endometrial carcinoma (8, 11.76%), vulval carcinoma (5, 7.35%) vaginal carcinoma (2, 2.94%), and leiomyosarcoma of uterus (1, 1.47%). Increased frequency of cervical and endometrial carcinomas were seen in Group-I cases, while vulval carcinoma was seen more commonly in Group-II cases (p=0.004). Conclusion: A very high frequency of cervical carcinoma was seen in our patients. There is need for more public awareness to integrate routine Gynae-Pap screening. Keywords: Postmenopausal, female genital tract, malignancy, frequency, types, women, carcinoma, Pap smear